2010
DOI: 10.1515/jpm.2009.133
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of pregnancy conceived despite the presence of an intrauterine device (IUD)

Abstract: OBJECTIVE Intrauterine devices (IUDs) are used for contraception worldwide; however, the management of pregnancies with an IUD poses a clinical challenge. The purpose of this study was to determine the outcome of pregnancy in patients with an IUD. STUDY DESIGN A retrospective cohort study (December 1997-June 2007) was conducted. The cohort consisted of 12,297 pregnancies, of which 196 had an IUD. Only singleton pregnancies were included. Logistic regression analysis was used to adjust for potential confounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 52 publications
3
33
0
3
Order By: Relevance
“…Moreover, this condition has been identified in a subset of patients with a short cervix [3942], cervical insufficiency [43,44], and other conditions which confer increased risk for preterm delivery, such as an intrauterine device in pregnancy [45], vaginal bleeding [46], and placenta previa [47]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this condition has been identified in a subset of patients with a short cervix [3942], cervical insufficiency [43,44], and other conditions which confer increased risk for preterm delivery, such as an intrauterine device in pregnancy [45], vaginal bleeding [46], and placenta previa [47]. …”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous abortion was significantly less in the withdrawal method users compared to cases with retained IUD, findings in agreement with those of other studies, which suggest that the endometritis and disturbed implantation site may be responsible for the increased abortion rate. 5,7,12 Moreover, Deveer et al found that the risk of miscarriage increased significantly when the IUD is retained, compared to when it is removed. 8 Brahmi et al demonstrated that if the IUD is left in the uterus, the rate of miscarriage, preterm labour, and chorioamnionitis are increased.…”
Section: Differences In Results and Conclusion In Relation To Other mentioning
confidence: 99%
“…Because amniocentesis was not performed in any of the patients, we could not determine the prevalence of microbial invasion of the amniotic cavity. Sun Kwan Kim et al [16] have demonstrated that pregnancies with an IUD had a higher rate of intra-amniotic infection and a higher rate of histological chorioamnionitis. According to our results, we can suggest that IUD removal in early gestation reduces the risk for obstetric complications, but we can not conclude that it eliminates because we did not have a third group of patients who conceived without an IUD.…”
Section: Discussionmentioning
confidence: 99%